2019
DOI: 10.2217/imt-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cardiac Tamponade During Nivolumab Of Lung Cancer with Intrapericardial Bleomycin: Case Report

Abstract: Immuno-checkpoint inhibitor response and immune-related adverse events remain controversial issues. Managing pericardial effusion during programmed cell death 1 inhibitor treatment is challenging. Here, we report a case of successfully managed cardiac tamponade caused by nivolumab-induced pseudoprogression. A 62-year-old male diagnosed with advanced lung adenocarcinoma started on nivolumab. Seven days later, he experienced cardiac tamponade and required pericardiocentesis, and other lesions were larger on comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Despite the low incidence of pericardial effusion under nivolumab in these studies, 13 cases have been reported in the literature since 2016 [1221]. We report on 3 new cases of early and late-onset pericardial effusion in patients with NSCLC treated with nivolumab.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the low incidence of pericardial effusion under nivolumab in these studies, 13 cases have been reported in the literature since 2016 [1221]. We report on 3 new cases of early and late-onset pericardial effusion in patients with NSCLC treated with nivolumab.…”
Section: Discussionmentioning
confidence: 91%
“…Table lists the publications on pericardial effusion or pericardial tamponade following anti‐PD‐1 immunotherapy in lung cancer patients . Increasing pericardial effusion is often observed within three months of the start of anti‐PD‐1 immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…reported that pericardial effusion was effectively managed using corticosteroids, implying that their patients had irAEs. Other studies have indicated that some pericardial effusions in lung cancer patients with tamponade may be caused by pseudoprogression …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations